Kinetics and mechanism of the forward and reverse reactions between N,N′-dimethyl-4,4′-bipyridinium and hexacyanoferrate(II) - Andrade de Oliveira, Luiz Antonio [UNESP]; Haim, Albert (American Chemical Society (ACS), 1982)
The kinetics of the hexacyanoferrate(III)-N,N′-dimethyl-4,4′-bipyridinium radical (MV+) reaction was studied by a laser flash photolysis technique. The radical was generated, in the presence of Fe(CN)6 3-, by quenching the excited state *Ru(bpy)3 2+ with MV2+. The second-order rate constant for the Fe(CN)6 3--MV+ reaction is (7.6 ± 0.5) × 109 M-1 s-1 at 23°C and ionic strength 0.10 M. Comparison with the rate constants calculated for the diffusion-controlled reaction (4.7 × 109 M-1 s-1) and the activation-controlled reaction (5.2 × 1012 M-1 s-1, on the basis of self-exchange rate constants of 8.0 × 105 M-1 s-1 and 1.9 × 104 M-1 s-1 for the MV2+/+ and Fe(CN)6 3-/4- couples, respectively) leads to the conclusion that the Fe(CN)6 3--MV+ reaction is diffusion controlled. The rate constant for the Fe(CN)6-MV2+ reaction, calculated from the rate constant for the Fe(CN)6 3--MV+ reaction and the appropriate equilibrium constant, is 2.4 × 10-5 M-1 s-1 at 23°C and ionic strength 0.10 M. Microscopic reversibility considerations require that the Fe(CN)6 4--MV2+ reaction be controlled by the dissociation of the successor complex Fe(CN)6 3-|MV+. The thermal and optical electron transfers in the ion pair Fe(CN)6 4-|MV2+ and in related systems are analyzed and discussed. © 1982 American Chemical Society.